Study guides

Q: How do you Simplify 4 over 2X plus 9 over 3X?

Write your answer...

Submit

Related questions

3x(2x + 1) over (2x - 1)(2x + 1) Cancel out the 2x + 1 Answer: 3x/2x - 1

3x + 7y

5x - 8a + 4a - 2x + a = 3x - 3a

3x^2 + x + 2x^2 = 5x^2 + x

3x-2y+9+9y-x = 2x+7y+9

3x + 2x - 8x + 2x = -x

simplify it, 7x-12=x+2+2x-3x 7x=2+12+3x-3x 7x=14 x=2

2x + 3x = 5x.

2x + 3x = 5x

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x + 2) - 4(x + 2) = (x + 2)(3x - 4).

2x+3x = 5x

-3x2 + 16x + 12 = -3x2 + 18x - 2x + 12 = -3x*(x - 6) - 2(x - 6) = -(3x + 2)*(x - 6)

-2x^4+16 +2x^4+9-3x^5=-3x^5+25. There is no "answer" because there is no equation.

No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²

2x + 3x + 6 = 5x + 6

6x^2

5x+8x+3x-2x = 14x

3x+3-2x=3 x+3=3 x-0

2x+x+5+3x-6=6x-1

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

3x+56 = 2x+4 3x-2x = 4-56 x = -52

3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20

3x+5 = 2x+13 3x-2x = 13-5 x = 8

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

3x-7y